PENGARUH LAMA FERMENTASI LIMBAH KULIT NENAS (Ananas comosus L. Merr) TERHADAP KADAR BIOETANOL SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI SMA MATERI BIOTEKNOLOGI - Dedy Purnomo; Sri Wulandari; Imam Mahadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to know influence of fermentation time pineapple skin waste (Ananas comosus L. Merr) againts bioethanol level and produce a design biology learning module at senior high school biotechnology material. Therefore a survey has been conducted in Kualu Nenas village of Kampar district Riau province to obtain the information as a raw for research and instruments for designing learning module. Experimental research by conducted a long fermentation experiment for 24 hours, 48 hours, 72 hours, 96 hours and 120 hours of pineapple skin waste with 5 treatments 3 replicates whewe the substrate was hudrolyzed first with 5% sulfuric acid and continued with the developments of learning module from experimental research (only analyze and design stages). The research data were analized using variances analysis techniques and continued with Duncan’s Multiple Range Test (DMRT) of the 5% level. The results of the study indicate that fermentation time affects the bioethanol level and decreases the pH value, but does not affect temperature changes. The highest average bioethanol content was found at 96 hours (4 days) of fermentation which was 9.90%. All research data can be used to design senior high school biology learning module in conventional biotechnology material class XII with project based learning models. However, before the module design is used on a wider scale it is recomended that a feasibility test and effectiveness be carried out on a limited scale.Key Words: Fermentation, Pineapple Skin Waste, Bioethanol, Biology Learning Module